The enigmatic genus Stenichnoteras Scott from the Seychelles (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2014)
The genus Stenichnoteras, known from the Seychelles and represented by a single known species, St. montanum, is redescribed and redefined. The morphological structures of St. montanum are described and illustrated in detail. Similarities and possible affinities with other genera of Cyrtoscydmini are discussed, and it is concluded that Stenichnoteras may be closely related to Euconnus, despite an apparent difference in the shape of prothorax and some mesoventral structures.